Production of 3D printed PLA material for medical phantom in radiotheraphy - Rahimi, Aiman Rasyidah Mohd (2020)
The objective of this study is to produce 3D printed phantom in slab size using polylactic acid (PLA) material. The other two specific objectives are to design and slice the model using available modelling and slicing software and to compare the internal geometry of PLA between infill densities of 10%, 20% 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100% using slicing software (Cura). The materials in this study included PLA material, CAD software (Thinkercad), slicing software (Cura) and MyVista Cube 200 printer. The process of 3D printing was initially conducted by using CAD software that was used for object modelling. Then, the model was saved in STL file and was directly exported to slicing software. The printing parameters have been inserted and the model was sliced into horizontal layers to estimate the time taken needed in printing. Then, the process of 3D printing was done by using MyVista Cube 200 printer. The results shows that the 3D model was successfully designed using Thinkercad, and being printed in slab size with good fabrication quality. Besides, the internal geometry illustrated in Cura software show that the space or gap between the materials decrease with infill densities. As a conclusion, the 3D printed PLA phantom of 30% of infill density was successfully made that can be used for dosimetry in radiotherapy for further study.